Forced Running Endurance Is Influenced by Gene(s) on Mouse Chromosome 10 - Kvedaras, Mindaugas; Minderis, Petras; Fokin, Andrej; Ratkevicius, Aivaras; Venckunas, Tomas; Lionikas, Arimantas (Frontiers in Physiology, 2017)
Phenotypic diversity between laboratory mouse strains provides a model for studying the underlying genetic mechanisms. The A/J strain performs poorly in various endurance exercise models. The aim of the study was to test if endurance capacity and contractility of the fast- and slow-twitch muscles are affected by the genes on mouse chromosome 10. The C57BL/6J (B6) strain and C57BL/6J-Chr 10A/J/NaJ (B6.A10) consomic strain which carries the A/J chromosome 10 on a B6 strain background were compared. The B6.A10 mice compared to B6 were larger in body weight (p<0.02): 27.2 ± 1.9 vs. 23.8 ± 2.7 and 23.4 ± 1.9 vs. 22.9 ± 2.3 g, for males and females, respectively, and in male soleus weight (p<0.02): 9.7 ± 0.4 vs 8.6 ± 0.9 mg. In the forced running test the B6.A10 mice completed only 64% of the B6 covered distance (p<0.0001). However, there was no difference in voluntary wheel running (p=0.6) or in fatigability of isolated soleus (p=0.24) or extensor digitorum longus (EDL, p=0.7) muscles. We conclude that chromosome 10 of the A/J strain contributes to reduced endurance performance. We also discuss physiological mechanisms and methodological aspects relevant to interpretation of these findings.